2016
DOI: 10.4172/2167-0501.1000220
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Mineral Regulation Under Heavy Metal Stress: Advances and Prospects

Abstract: Heavy metals (HMs) contaminate the soil through various natural and anthropogenic resources and are transported to the plant systems. These heavy metals are translocated within the plant system by the apoplast and symplast through various transporters such as HMAs, ZIP, ABC. HMs disturb plant metabolism, cause oxidative stress and nutrient dearth. Many researchers have applied exogenous minerals to alleviate these negative impacts caused by HMs. Minerals mitigate the HMAs induced negative impacts by the enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…One of the major consequences of metal/metalloid stress is nutrient deficiency, as metal/metalloids compete with essential mineral elements for uptake into the plant [43]. Nutrient homeostasis could therefore reduce metal/metalloid accumulation, and thereby their toxicity, to enhance many physiological mechanisms under Cd stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major consequences of metal/metalloid stress is nutrient deficiency, as metal/metalloids compete with essential mineral elements for uptake into the plant [43]. Nutrient homeostasis could therefore reduce metal/metalloid accumulation, and thereby their toxicity, to enhance many physiological mechanisms under Cd stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Such detoxification prevents cell injury and tissue dysfunction. This reduction in phenolic compounds might also be attributed to the role of their hydroxyl and carboxyl group in the scavenging of free radicals and chelating heavy metals (Yadav et al, 2016) or due to the utilization of simple phenols in the formation of complex compounds like flavonoids, tannins, and lignins (Mondal et al, 2015).…”
Section: Malondialdehyde (Mda) Contentmentioning
confidence: 99%
“…Among the remedies for abiotic stress, nutrient regulations or management are considered as the cost effective and eco-friendly techniques Yadav et al, 2016). It has been reported that plant nutrients (micro and macro) play important roles in growth and development (White and Brown, 2010;Waraich et al, 2011;Tripathi et al, 2014Tripathi et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%